1989
DOI: 10.1200/jco.1989.7.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ambulatory ECG monitoring during fluorouracil therapy: a prospective study.

Abstract: Although there have been anecdotal reports of cardiac toxicity associated with fluorouracil (5-FU) therapy, this phenomenon has not been studied in a systematic fashion. We prospectively performed continuous ambulatory ECG monitoring on 25 patients undergoing 5-FU infusion for treatment of solid tumors in order to assess the incidence of ischemic ST changes. Patients were monitored for 23 +/- 4 hours before 5-FU infusion, and 98 +/- 9 hours during 5-FU infusion. Anginal episodes were rare: only one patient had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
5

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 16 publications
5
93
0
5
Order By: Relevance
“…Several causative mechanisms for 5-FU cardiotoxicity have been postulated, including an autoimmune response to damaged cells (Stevenson et al, 1977), increased oxygen demand in patients receiving 5-FU (Rezkalla et al, 1989), coronary spasm (Burger and Mannino, 1987) due to protein kinase C-mediated vasoconstriction (Mosseri et al, 1993) and the 5-FU contaminant fluoroacetate (FAC) (Lemaire et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several causative mechanisms for 5-FU cardiotoxicity have been postulated, including an autoimmune response to damaged cells (Stevenson et al, 1977), increased oxygen demand in patients receiving 5-FU (Rezkalla et al, 1989), coronary spasm (Burger and Mannino, 1987) due to protein kinase C-mediated vasoconstriction (Mosseri et al, 1993) and the 5-FU contaminant fluoroacetate (FAC) (Lemaire et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a review of 377 cases of 5-FU associated cardiotoxicity confirmed that the majority of cases of cardiotoxicity occur in the setting of continuous infusion [6]. And while overall cardiac toxicity with 5-FU administration may vary, rates are uniformly higher in patients with underlying heart disease, including coronary artery disease (CAD), structural heart disease, and cardiomyopathies [2,16].…”
Section: Epidemiologymentioning
confidence: 99%
“…A study by Rezkalla et al [16] demonstrated ischemic and arrhythmic ECG changes, to include ST-segment deviation and QT-prolongation, in nearly 68% of patients receiving infusions of 5-FU. Others have noted incidences of asymptomatic diagnostic ECG changes in up to 88% of patients during 5-FU infusion, with nearly 7% demonstrating elevated cardiac enzymes [12,35].…”
Section: Silent Ischemia and Myocardial Infarctionmentioning
confidence: 99%
“…Its chief side-effects are myelosuppression, diarrhoea, vomiting and mucositis. However, over the last decade, the number of reports of cardiotoxicity and neurotoxicity attributed to FU has rapidly increased, probably because of the use of higher doses in continuous perfusion (Moertel et al, 1964;Rezkalla et al, 1989;Moore et al, 1990;Gamelin et al, 1991; De Fomi et al, 1992;Robben et al, 1993;Anand, 1994). The precise biochemical mechanism underlying these two side-effects remains unclear, although several investigators have postulated, but never demonstrated experimentally, that FU might be transformed into fluoroacetate (FAC), a highly cardiotoxic and neurotoxic poison (Koenig and Patel, 1970;Okeda et al, 1990).…”
mentioning
confidence: 99%